Buerger Allen Exercise terhadap Sirkulasi dan Sensori Perifer pada Pasien dengan Diabetes Melitus - Fina Mahardini; Debie Dahlia; Dikha Ayu Kurnia; Etty Rekawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to systematically evaluate the results of studies assessing the effectiveness of the Buerger Allen Exercise (BAE) in improving circulation and peripheral sensory status in patients with Diabetes Mellitus (DM). The method used is a systematic review in which researchers carry out a comprehensive and systematic search based on PRISMA's recommendations for research articles using randomized controlled trial (RCT) methods, quasi-experiments, and cohorts using the keywords